Hesychasm and Psychedelics: Altered States, Purgation, and the Question of Authentic Mysticism - Thomas Cattoi (Journal of Contemplative Studies, 2024)
The purpose of this essay is to introduce the reader to the tradition of Hesychasm—a form of monastic asceticism rooted in the tradition of the Desert Fathers and given a systematic articulation by the Byzantine author Gregory Palamas (1296–1359)—and to consider how the mystical experiences described in Palamas’s Triads compare to the altered states at the center of contemporary psychedelic research. After reviewing the chief claims of the hesychastic tradition about the nature and purpose of ascetic practice, the essay will consider the methodological challenges psychedelic researchers face when assessing experiences induced by psychedelic substances. The last section will turn to the discipline of Comparative Theology as a helpful framework to bring into dialogue the hesychastic understanding of deification as a trajectory grounded in the reception of the sacraments and the therapeutic impact of psychedelic experiences. The essay will uncover different points of contact between hesychastic and psychedelic experience but will also foreground a number of irreducible differences between the two, reflecting the specific anthropological and soteriological claims of the hesychastic tradition. The conclusion will advocate for greater epistemic modesty—warning from overhasty identification of mystical states and psychedelic experiences—but also invite theologians and psychedelic researchers to greater reciprocal openness to each other’s insights.